The impact of Transformational leadership styles and Organizational Culture on the Performance of MSME Employees through mediation of Organizational Learning - Ikhram W., M. Abdi Dzil; Fuadiputra, Iqbal Ramadhani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the extent of human resource issues in MSMEs. Human Resources at MSMEs are interesting because the more advanced times companies and organizations are required to continue to develop and innovate cannot be separated from the MSMEs themselves. The leadership style is one of the points in the company to develop. Not only the culture of the organization or company also has a link to building learning in the organization which will have an impact on the performance of employees in this company. This research is a qualitative method which is carried out in MSMEs in the East Java region. Researchers used survey methods and in-depth interviews in the data analysis process. In testing the validity of the data, the author uses the data triangulation technique from resource persons compared to other informants. Meanwhile, data analysis was performed using the classical assumption test. This research is expected to find the impact of transformational leadership, organizational culture, and performance in MSMEs.